Effect of Parasocial Commitment and Breakup with a Fictional Character on Purchase Intention - Grover, Abhay; Arora, Nilesh (Prabandhan: Indian Journal of Management, 2024)
Purpose : To mitigate the danger of non-fictional character transgression, this study used the investment model and research on fictional character endorsement. Furthermore, it attempted to investigate how parasocial breakup (PSB) mediated the relationship between commitment to parasocial relationships (PSR) and purchase intention (PI) for the fictional character. Design/Methodology/Approach : A mixed-methods approach was employed in the subject selection process. The states and districts were chosen using a random sampling process based on a lottery system. Additionally, the quota for each chosen state and district was fixed using a quota sampling technique. The current study selected five states from 29 states, as well as five districts within each state, using the lottery method of random sampling technique. Furthermore, the quota for each chosen state was determined using the quota sampling approach. Findings : The present study’s findings showed a positive relationship between commitment to PSR with a fictional character and PI. However, PSB appeared to negatively mediate the relationship between commitment to PSR and PI concerning the fictional character. Practical Implications : Fictional characters could serve as a potent marketing tool capable of effectively promoting consumer parasocial commitment and PI. Therefore, companies should contemplate incorporating fictional characters in their marketing strategies, particularly in product categories where consumers exhibit low involvement and require a relationship-building experience with the brand. Originality/Value : As far as we know, this is the first study to analyze the interplay between commitment in a PSR, PSR break-up, and PI.